Positive Leadership : Qualitative Leadership Research Using Deductive Pattern Matching Approach - Khatri, Puja; Kaushik, Neeraj; Kaushik, Neeraj; Kumari, Preeti; Kumari, Preeti (Prabandhan: Indian Journal of Management, 2022)
As the business environment has become more complex, the need for a positive leader has emerged. The present research attempted to study positive leadership using review and qualitative methods. The study focused on exploring the dimensions of positive leadership through a systematic review of literature. Additionally, we employed a case study method to map Ratan Tata’s leadership traits with a positive leader using deductive thematic analysis and pattern matching approach supported by word cloud and sentiment analysis. Twenty-nine interviews and speeches from 1994 to 2020 were transcribed and coded in NVivo to frame Word query. Also, sentiment analysis on tweets connected with #Ratan Tata was collected and exported using NCapture in QSR NVivo software. This study provided explicit dimensions of positive leadership and qualitatively confirmed Ratan Tata as a positive leader using a pattern-matching approach. This was supported by word cloud and sentiment analysis. The results unfolded the dimensions of positive leaders for future researchers to explore empirically. It can also provide guidelines to practitioners for designing a training module for budding entrepreneurs and leaders to navigate through challenging times.